Comparative Investigation on CSMA/CA-Based MAC protocols for Scalable Networks - Abbas, Ali. M. H.; Ali, Jahan; Rahman, Md. Arafatur; Azad, Saiful (IEEE, 2016)
The Backoff mechanism is one of the key factors of Medium Access Control (MAC) protocol which is scheduling to share the medium among the stations in order to transmit data in Wireless Local Area Network networks (WLAN). More in detail, the wireless network allows multiple stations to interact with each other on a same medium. Therefore, if two or more stations transmit at the same time then the collision happens. To avoid or reduce the probability of collision, the Backoff mechanism takes the responsibility by placing the stations in the waiting queue before transmission. Hence, Backoff mechanism is a very critical element and researchers as well as the manufactures are always looking for more efficient Backoff mechanism for WLAN. In particular, it will be more critical while the number of node increases and becomes large network, referred to as scalable network. Scalability is a critical requirement if we want the networking technologies to reach their full potential. In this paper, we investigate this issue by exploiting the existing CSMA/CA-Based MAC protocols in comparatively large networks. The simulation results revile some important issues and challenges in order to provide MAC solutions for scalable networks. The outcome of this research assists to design a new MAC protocol for such networks.